Spectroscopic analysis tool for intEgraL fieLd unIt daTacubEs (satellite): case studies of NGC 7009 and NGC 6778 with MUSE. Issue 2 (10th March 2022) - Akras, S; Monteiro, H; Walsh, J R; García-Rojas, J; Aleman, I; Boffin, H; Boumis, P; Chiotellis, A; Corradi, R M L; Gonçalves, D R; Gutiérrez-Soto, L A; Jones, D; et al.
ABSTRACT: Integral field spectroscopy (IFS) provides a unique capability to spectroscopically study extended sources over a 2D field of view, but it also requires new techniques and tools. In this paper, we present an automatic code, Spectroscopic Analysis Tool for intEgraL fieLd unIt daTacubEs, satellite, designed to fully explore such capability in the characterization of extended objects, such as planetary nebulae, H ii regions, galaxies, etc. satellite carries out 1D and 2D spectroscopic analysis through a number of pseudo-slits that simulate slit spectrometry, as well as emission line imaging. The 1D analysis permits direct comparison of the integral field unit (IFU) data with previous studies based on long-slit spectroscopy, while the 2D analysis allows the exploration of physical properties in both spatial directions. Interstellar extinction, electron temperatures and densities, ionic abundances from collisionally excited lines, total elemental abundances, and ionization correction factors are computed employing the pyneb package. A Monte Carlo approach is implemented in the code to compute the uncertainties for all the physical parameters. satellite provides a powerful tool to extract physical information from IFS observations in an automatic and user configurable way. The capabilities and performance of satellite are demonstrated by means of a comparison between the results obtained from the Multi Unit Spectroscopic Explorer (MUSE) data of the planetary nebula NGC 7009 with the results obtained from long-slit and IFU data available in the literature. The satellite characterization of NGC 6778 based on MUSE data is also presented.